Defect Detection on Welding Joint using Acoustic Emission Technology - Miminorazeansuhaila, Loman; Che Ku Eddy Nizwan, Che Ku Husin; Norshalawati, Mat Yusof (2013)
This study was carried out as an initial study to investigate the potential of acoustic emission technology to to detect the welding defects on steel. Two pieces of mild steels were welded together in the middle part of steel. The welding specimen was made with defects and without defects. This was purposely done to compare the difference that might be existed between these two types of specimen. The piezoelectric sensor was located on both of the welding specimens while specimens were pressurised to promote cracks. During the experimental work, the acoustic emission signatures were acquired using the AE node acoustic emission data acquisition system. The signals were analysed using the AEWin software in order to verify the defects. Comparison made from the analysis showed that there were differences between the welding specimen with defects and without defects. From the analysis done, it shows that the welding specimen with defect produced higher value of acoustic emission parameter such as peak amplitude and RMS.